Australia's energy quandary: options and implications for the future - Hubbard, Christopher (2007)
Australia has been part of the global nuclear equation for over sixty years and cannot avoid its nuclear future. Internationally, it must now decide how best to balance rising demand for its uranium with the dangers of nuclear weapons proliferation inherent in exporting fissionable materials to an increasingly unstable world.The most effective nuclear policy choice for Australia would be to accept that Australian uranium sales can be used both to contribute towards global efforts to reduce greenhouse gas emissions while simultaneously reducing, or at the very least, not enhancing the risks of nuclear weapons proliferation associated with uranium exports to clandestine weapon aspirant states (including transfer to non-state actors).The challenge for Australian nuclear policy is now to use its new-found market power and undoubted non-proliferation credentials in coordinated ways which enhance resistance against nuclear proliferation from all sources using all opportunities, including those afforded by an indigenous power industry.In this context Australia can show the way forward in, for example, its use of proliferation-resistant reactor and full scale fuel cycle technologies while exporting uranium with enhanced counter-proliferation supply conditions.